Functional traits influence patterns in vegetative and reproductive plant phenology – a multi‐botanical garden study. Issue 6 (26th July 2022) - Sporbert, Maria; Jakubka, Desiree; Bucher, Solveig Franziska; Hensen, Isabell; Freiberg, Martin; Heubach, Katja; König, Andreas; Nordt, Birgit; Plos, Carolin; Blinova, Ilona; Bonn, Aletta; Knickmann, Barbara; et al.
Summary: Phenology has emerged as key indicator of the biological impacts of climate change, yet the role of functional traits constraining variation in herbaceous species' phenology has received little attention. Botanical gardens are ideal places in which to investigate large numbers of species growing under common climate conditions. We ask whether interspecific variation in plant phenology is influenced by differences in functional traits. We recorded onset, end, duration and intensity of initial growth, leafing out, leaf senescence, flowering and fruiting for 212 species across five botanical gardens in Germany. We measured functional traits, including plant height, absolute and specific leaf area, leaf dry matter content, leaf carbon and nitrogen content and seed mass and accounted for species' relatedness. Closely related species showed greater similarities in timing of phenological events than expected by chance, but species' traits had a high degree of explanatory power, pointing to paramount importance of species' life‐history strategies. Taller plants showed later timing of initial growth, and flowered, fruited and underwent leaf senescence later. Large‐leaved species had shorter flowering and fruiting durations. Taller, large‐leaved species differ in their phenology and are more competitive than smaller, small‐leaved species. We assume climate warming will change plant communities' competitive hierarchies with consequences for biodiversity.